Transformasi Teknologi: E-Procurement Sebagai Garda Terdepan dalam Memerangi Korupsi, Kolusi, dan Nepotisme pada Pengadaan Barang dan Jasa - Audrey Syabani Latimena; Neneng Wety Isnawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Procurement of goods and services is a key element in the operational activities of companies, playing a central role in maintaining business continuity and ensuring the fulfillment of production or service needs. However, conventional procurement is vulnerable to Corruption, Collusion, and Nepotism (CCN) practices. This research discusses the urgency of implementing e-procurement as a solution to address corruption challenges in the procurement of goods and services in Indonesia. The implementation of e-procurement is expected to enhance transparency, efficiency, and accountability at every stage of procurement. Data shows a high frequency of corruption cases in the procurement of goods and/or services in Indonesia, prompting the government to implement Presidential Regulation Number 50 of 2019, which mandates the use of electronic procurement. This study employs a qualitative descriptive method with a literature review. Data from various literature sources indicate that e-procurement can reduce the opportunities for CCN practices through transparency, increased vendor participation, and accountable digital records. Although the transformation of e-procurement has a positive impact on combating CCN, the high level of corruption cases suggests challenges in implementation that need to be addressed. Comprehensive evaluation, organizational culture improvement, and strengthening of oversight and law enforcement are key to success. Measures such as training, awareness campaigns, and continuous improvement are required to ensure that e-procurement not only becomes a formality but also makes a real contribution to reducing the CCN index and enhancing integrity in the procurement of goods and services in Indonesia.